(untitled) (Agricultural Engineering, 2017)
The objective of the research was assessment of the sowing quality of radish seeds with the sowing unit of “MAX PNEUAMTIC” S 156 pneumatic seeder. Tests were carried out on the original laboratory stand. They proved that at the assumed range of the working speed within 2.5 to 4.0 km·h−1 and rotations of the sowing disc between 23 and 37 rot·min−1, the most favourable results concerning precision of seeds spacing in a row were obtained at the speed between 2.5 and 3.0 km·h−1. The increase of the speed above 3.0 km·h−1 caused deterioration of the seeds sowing quality through statistically significant reduction of the single sowing participation and the increase of the empty sowings participation.